Serum and Urinary Neutrophil Gelatinase-Associated Lipocalin Are Not Associated With Serum Redox Parameters in Amateur Athletes After an Ultramarathon - Loureiro, Adriano César Carneiro; Nocrato, Gabriella Fontenele; Correia, André Luis Lima; de Matos, Robson Salviano; Filho, Júlio César Chaves Nunes; Daher, Elisabeth De Francesco; Pinto, Flávio Henrique Macedo; de Oliveira, Ariclécio Cunha; Ceccatto, Vania Marilande; Fortunato, Rodrigo Soares; de Carvalho, Denise Pires (Frontiers in Physiology, 2022)
Objective: To evaluate the relationship between oxidative stress and levels of NGAL in blood and urine of amateur athletes after participating in a 100 km ultramarathon. Methodology: The sample was composed of seven athletes, submitted to anthropometric assessment, cardiopulmonary exercise test, collection of urine and blood, measurement of body weight and rate of perceived exertion (RPE), along with verification of competition duration, heart rate (HR), energy expenditure and oxygen consumption (V’O2’’) during the event. At the end of the race, the energy consumption during its period was verified. The analyses were based on the means (M) and respective standard deviations (SD) found, with statistical significance set at 5% (p < 0.05). The paired t-test was used for comparison between the periods before and after the competition, and Pearson’s correlation coefficient was used to measure the linear correlation between the quantitative variables. Results: The sample had body mass index (BMI) of 25.75 kg/m2  3.20, body fat percentage of 18.54%  4.35% and V’O2’’max of 48.87%  4.78. In the comparison before and after the event, there were higher concentrations of glucose, cortisol, glutathione peroxidase (GPx) and neutrophil gelatinase-associated lipocalin (NGAL), which is a glycoprotein that is part of the lipocalin family (p < 0.01), as well as higher levels of lactate, creatinine, microalbuminuria and glomerular filtration rate (GFR) (p < 0.001) afterward. After the competition, the only significant correlation was between serum NGAL and creatinine, classified as strong and positive (r: 0.77; p < 0.05). There was a significant reduction (p < 0.05) of body weight after the event (72.40 kg  9.78) compared to beforehand (73.98 kg  10.25). In addition, we found an increase in RPE (p < 0.001) after the race. The competition lasted 820.60 minutes ( 117.00), with an HR of 127.85 bpm ( 12.02), energy consumption of 2,209.72 kcal + 951.97, energy expenditure of 7,837.16 kcal + 195.71, and relative V’O2’’max of 28.78 ml/kg/min-1 ( 4.66). Conclusion: The lack of correlation between oxidative stress biomarkers and NGAL serum and urine suggests that NGAL is more sensitive to inflammatory processes than ROS levels.